Hormônio alfa estimulante dos melanócitos (α-MSH) não modifica as convulsões induzidas por pentilenotetrazol e por pilocarpina em camundongos - Temp, Fernanda Rossato (2013)
Alpha-melanocyte stimulating hormone (α-MSH) is a pro-opiomelanocortin (POMC)-derived peptide involved in different neurological functions that also exerts anti-inflammatory effects, including in the central nervous system (CNS). Although inflammation has been implicated in seizures and epilepsy, no study has systematically investigated whether α-MSH modifies seizures. Therefore, in the current study we determined whether α-MSH alters pentylenetetrazol (PTZ)- and pilocarpine-induced seizures. Adult male Swiss mice were injected with α-MSH (1.66, 5 or 15 μg/3 μL, intracerebroventricular (i.c.v.) or systemic (0.1, 0.3 or 1 mg/kg, intraperitoneally (i.p.)). Five to sixty minutes after the injection of the peptide, animals were injected with PTZ (60 mg/kg, i.p.) or pilocarpine (370 mg/kg, i.p.). Latency to myoclonic jerks and tonic clonic seizures, number of seizure episodes, total time spent seizing and seizure intensity, assessed by the Racine and Meurs scales were recorded. Interleukin 1 beta (IL-1β) levels in the hippocampus were measured by a commercial enzyme-linked immunoabsorbent assay (ELISA). Neither intracerebroventricular (1.66, 5 or 15 μg/3 μL, i.c.v.) nor systemic (0.1, 0.3 or 1 mg/kg, i.p.) administration of α-MSH altered PTZ- and pilocarpine-induced seizures. IL-1β levels in the hippocampi were not altered by α-MSH, PTZ or pilocarpine. Although inflammation has been implicated in seizures and epilepsy and α-MSH is a potent antiinflammatory peptide, our results do not support a role for α-MSH in seizure control.